Learning to Coexist: Education, Cultural Values, and Religious Harmony in Kedang Society - Lamabawa, Dahlan; Amin, Saifuddin; Amirah, Amirah; Billah, Muktashim (Dinamika Ilmu, 2025)
This research explores the resilience of interreligious harmony in Kedang, Lembata Regency, East Nusa Tenggara, by focusing on the intersection of local culture, religion, and governance. The study identifies three central pillars in the philosophy of life for the Kedang people: the Customary, Religious, and Governmental pillars, which together foster a strong social fabric. Key aspects of Kedang culture, including traditional architecture, music, rituals, and customs, are examined for their role in sustaining peaceful coexistence among different religious groups. A phenomenological approach is used to understand these practices authentically, with data collected through participant observation, in-depth interviews, and documentation. The research employs purposive sampling to select informants, including community, religious, youth, and traditional leaders, as well as government officials. Through SWOT analysis, the study assesses the strengths, weaknesses, opportunities, and threats related to interfaith relations in Kedang, proposing strategic measures for reinforcing religious harmony. The findings contribute to a broader understanding of cultural and religious dialogue, offering a model for promoting peace and unity in diverse communities, both within Indonesia and globally.